2001
DOI: 10.1212/wnl.56.11.1505
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of interferon-beta-1a in secondary progressive MS

Abstract: Interferon-beta-1a used in SPMS showed significant effects on all MRI measures, particularly in patients with relapses in the 2 years before the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(94 citation statements)
references
References 23 publications
2
90
0
2
Order By: Relevance
“…Over the last decade, a number of immunomodulatory and immunosuppressive therapies have been approved for clinical use based primarily on demonstration of their ability to suppress focal inflammatory activity, i.e., lesion formation, and clinical relapses (Comi et al, 2001;Leary et al, 2003;Li and Paty, 1999;Li et al, 2001;Miller et al, 1999;Paty and Li, 1993;Simon et al, 1998;Simon et al, 2000;Zhao et al, 2000). Development of these therapies has been critically dependent on MRI because of the ability of MRI to visualize lesion formation with an order of magnitude greater sensitivity than clinical observation is able to detect relapses The number and volume of MS lesions represent the "burden of disease" and are predictive of patients' clinical course over the long term (O'Riordan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, a number of immunomodulatory and immunosuppressive therapies have been approved for clinical use based primarily on demonstration of their ability to suppress focal inflammatory activity, i.e., lesion formation, and clinical relapses (Comi et al, 2001;Leary et al, 2003;Li and Paty, 1999;Li et al, 2001;Miller et al, 1999;Paty and Li, 1993;Simon et al, 1998;Simon et al, 2000;Zhao et al, 2000). Development of these therapies has been critically dependent on MRI because of the ability of MRI to visualize lesion formation with an order of magnitude greater sensitivity than clinical observation is able to detect relapses The number and volume of MS lesions represent the "burden of disease" and are predictive of patients' clinical course over the long term (O'Riordan et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…31,35 In analyzing the effects of NAbs, some authors have used the ever positive, always positive method, in which patients who were ever NAb-positive are compared to persistently NAb-negative subjects. 19,[21][22][23][24][25] Other studies use the so-called once positive, always positive method, in which only observations after the patient has become NAb-positive (often defined as two consecutive positive tiers) are compared to observations in NAb-negative subjects. [14][15][16]20,29,31 Each of these methods fails to account for subjects who revert to NAb-negative status after becoming NAb-positive.…”
Section: -49mentioning
confidence: 99%
“…There was a significant effect of treatment on relapse rates, and MRI measures including lesion load, and new or enlarging T2 lesions. 53 A subgroup analysis suggested that maximal benefit with IFNβ-1a treatment in SPMS was seen in patients who continued to experience relapses, tending to confirm the outcomes of the European and North American IFNβ-1b studies.…”
Section: Dovepressmentioning
confidence: 85%